Variations in neonatal mortality, infant mortality, preterm birth and birth weight in England and Wales according to ethnicity and maternal country or region of birth: an analysis of linked national data from 2006 to 2012 - Opondo, Charles (J Epidemiol Community Health, 2020)
BACKGROUND: Risks of adverse birth outcomes in England and Wales are relatively low but vary across ethnic groups. We aimed to explore the role of mother’s country of birth on birth outcomes across ethnic groups using a large population-based linked data set. METHODS: We used a cohort of 4.6 million singleton live births in England and Wales to estimate relative risks of neonatal mortality, infant mortality and preterm birth, and differences in birth weight, comparing infants of UK-born mothers to infants whose mothers were born in their countries or regions of ethnic origin, or elsewhere. RESULTS: The crude neonatal and infant death risks were 2.1 and 3.2 per 1000, respectively, the crude preterm birth risk was 5.6% and the crude mean birth weight was 3.36 kg. Pooling across all ethnic groups, infants of mothers born in their countries or regions of ethnic origin had lower adjusted risks of death and preterm birth, and higher gestational age-adjusted mean birth weights than those of UK-born mothers. White British infants of non-UK-born mothers had slightly lower gestational age-adjusted mean birth weights than White British infants of UK-born mothers (mean difference −3 g, 95% CI −5 g to −0.3 g). Pakistani infants of Pakistan-born mothers had lower adjusted risks of neonatal death (adjusted risk ratio (aRR) 0.84, 95% CI 0.72 to 0.98), infant death (aRR 0.84, 95% CI 0.75 to 0.94) and preterm birth (aRR 0.85, 95% CI 0.82 to 0.88) than Pakistani infants of UK-born Pakistani mothers. Indian infants of India-born mothers had lower adjusted preterm birth risk (aRR 0.91, 95% CI 0.87 to 0.96) than Indian infants of UK-born Indian mothers. There was no evidence of a difference by mother’s country of birth in risk of birth outcomes among Black infants, except Black Caribbean infants of mothers born in neither the UK nor their region of origin, who had higher neonatal death risks (aRR 1.71, 95% CI 1.06 to 2.76). CONCLUSION: This study highlights evidence of better birth outcomes among UK-born infants of non-UK-born minority ethnic group mothers, and could inform the design of future interventions to reduce the risks of adverse birth outcomes through improved targeting of at-risk groups.